PENGATURAN PENGELOLAAN PASAR DAN FAKTOR PENGHAMBATNYA (STUDI TERHADAP PENGELOLAAN PASAR WUE KECAMATAN WOLOMEZE KABUPATEN NGADA PROVINSI NUSA TENGGARA TIMUR) - Kampas, Paskalina Fridolin; Stefanus, Kotan Y; Lamataro, Cyrilius W T (Petitum Law Journal, 2025)
Market management regulations are a series of activities carried out to regulate, manage, and maximize market functions so that they run in an orderly, efficient, and profitable manner for all parties involved, such as traders, buyers, and the government. Market management regulations cover various aspects, including regulations, policies, and operational governance. The main problems of this study are (1) How is the management of Wue Market, Wolomeze District, Ngada Regency? (2) What are the inhibiting factors in the management of Wue Market, Wolomeze District, Ngada Regency? The type of research used is normative-empirical (applied) research. This research was conducted in Wue Village. The types of data used are secondary data and primary data. The data collection techniques used are literature studies and interviews. The results of this study indicate that (1) The management of the Wue Village market is the responsibility of the Village-Owned Enterprise (BUMDes). Although there are no specific regulations governing the management of the market, an agreement has been reached between the Regional Government (Pemda) and the Village regarding the use of land using the borrow-use method. (2) The inhibiting factors in market management in Wue Village are human resource factors, lack of facilities and infrastructure, limited budget for market management, lack of government support and public legal awareness.